China’s Belt And Road Initiative And Nigeria’s Infrastructural Development: Assessing The Risk And Benefits Of Railway Investment - Gbadebo, Adedeji (Universitas Airlangga, 2025)
Abstract China’s Belt and Road Initiative (BRI) has significantly impacted Nigeria's infrastructure development, particularly in railway projects. This study assesses the risks and benefits of BRI-funded railway investments, with a focus on their economic, social, and environmental implications. A structured survey was conducted among 300 respondents from the Federal Capital Territory and Keffi, Nasarawa State, using a stratified random sampling method. The data and hypotheses were analyzed using the chi-square statistical technique. While BRI investments in railway infrastructure enhance transportation, stimulate economic activity, and strengthen regional connectivity, concerns persist regarding debt sustainability, reliance on Chinese technology and labor, and governance transparency. The statistical analysis reveals that the purported benefits of BRI railway projects do not have a statistically significant impact on Nigeria's infrastructure development. Additionally, the associated risks, such as increased national debt and economic dependence, are not substantially greater than the benefits. The study recommends renegotiating BRI agreements to promote local enterprise involvement, conducting comprehensive cost-benefit analyses before securing new loans, and improving governance frameworks to ensure transparency and accountability. Moreover, long-term maintenance strategies and environmental impact assessments should be prioritized to sustain infrastructure effectiveness and minimize adverse effects. Overall, while the BRI holds considerable promise for Nigeria’s infrastructure development, a balanced approach is essential to maximize its benefits while addressing the associated risks. Keywords: belt and road initiative; nigeria; railway investment; debt sustainability; infrastructure development Abstrak Inisiatif Sabuk dan Jalan China (BRI) telah memberikan dampak signifikan terhadap pembangunan infrastruktur di Nigeria, khususnya pada proyek kereta api. Penelitian ini mengevaluasi risiko dan manfaat dari investasi kereta api yang didanai oleh BRI, dengan fokus pada implikasi ekonomi, sosial, dan lingkungan. Survei terstruktur dilakukan terhadap 300 responden yang berasal dari Wilayah Ibu Kota Federal dan Keffi, Kabupaten Nasarawa, dengan menggunakan metode sampel acak berstrata. Data dan hipotesis dianalisis menggunakan teknik statistik chi-square. Meskipun investasi BRI pada infrastruktur kereta api meningkatkan transportasi, merangsang aktivitas ekonomi, dan memperkuat konektivitas regional, masih terdapat kekhawatiran terkait keberlanjutan utang, ketergantungan pada teknologi dan tenaga kerja China, serta transparansi tata kelola. Analisis statistik menunjukkan bahwa manfaat yang diklaim dari proyek kereta api BRI tidak memiliki pengaruh yang signifikan secara statistik terhadap pembangunan infrastruktur di Nigeria. Selain itu, risiko terkait, seperti peningkatan utang nasional dan ketergantungan ekonomi, tidak jauh lebih besar daripada manfaat yang ada. Penelitian ini menyarankan untuk merundingkan kembali kesepakatan BRI guna mendorong partisipasi perusahaan lokal, melakukan analisis biaya-manfaat yang komprehensif sebelum memperoleh pinjaman baru, dan meningkatkan mekanisme tata kelola untuk memastikan transparansi dan akuntabilitas. Lebih lanjut, strategi pemeliharaan jangka panjang dan penilaian dampak lingkungan harus menjadi prioritas untuk menjaga efektivitas infrastruktur dan mengurangi dampak negatif. Secara keseluruhan, meskipun BRI memberikan potensi besar bagi pembangunan infrastruktur Nigeria, pendekatan yang seimbang diperlukan untuk memaksimalkan manfaatnya sekaligus mengurangi risiko yang terkait. Kata kunci: inisiatif sabuk dan jalan; nigeria; investasi kereta api; keberlanjutan utang; pembangunan infrastruktur